The Role of Elastin in Tendon and Ligament Disorders: Therapeutic Interventions in Orthopedics and Sports Medicine - Gorska, Weronika; Jasiński, Filip; Łukawski, Artur; Szałajska, Julia; Wojtach, Klaudia; Banyś, Filip; Wiak, Iga; Bochen, Konrad; Czyżewski, Filip; Dziegciarczyk, Anna (Quality in Sport, 2024)
Introduction Elastin is a key protein in tendons and ligaments, responsible for providing elasticity, which allows these tissues to withstand mechanical stress and maintain joint stability. However, elastin integrity can decline due to factors such as aging, genetics, or injury, leading to joint instability, chronic pain, and a heightened risk of further damage. This study examines the role of elastin- focused therapies in addressing such issues, with a focus on orthopedics and sports medicine. Objectives The objective of this review is to evaluate emerging elastin-based therapeutic strategies, such as platelet-rich plasma (PRP) therapy, bioengineered scaffolds, and microRNA-based treatments, and their potential to enhance recovery in musculoskeletal injuries by improving tissue elasticity and resilience. Materials and Methods A comprehensive review of the studies available on open access sources, including PubMed, Google Scholar, and the National Library of Medicine, was conducted. The focus was on current advancements in platelet-rich plasma (PRP) therapy, bioengineered scaffolds, and microRNA-based treatments. Studies assessing the efficacy of these approaches in promoting elastin synthesis, tissue flexibility, and repair outcomes were analyzed, particularly in cases involving conditions like Achilles tendinopathy, rotator cuff injuries, and ACL reconstructions. Conclusions Elastin plays a crucial role in tendon and ligament health, and emerging elastin- focused therapies show significant potential in enhancing recovery from musculoskeletal injuries. PRP therapy, bioengineered scaffolds, and microRNA- based treatments have demonstrated promising outcomes in improving tissue flexibility, supporting cell growth, and slowing degenerative processes. Further research and clinical trials are needed to optimize these therapies for long-term patient outcomes in orthopedic and sports medicine.